The cost effectiveness of remediating erosion gullies: a case study in the Fitzroy. Issue 2 (3rd April 2018) - Rust, Steven; Star, Megan
ABSTRACT: Grazing in the Fitzroy region has reduced ground cover and increased the exposure of erosion features to terrestrial water flows, resulting in gullies. The run-off that results from such soil degradation has led to elevated levels of sediment in the Great Barrier Reef, adversely affecting the health of the reef. Strategies to reduce gully erosion include: decreasing stocking rates on grazing land, revegetation of erosion features and the implementation of specific infrastructure including fencing and earth works. Using data provided by the Fitzroy Basin Association Inc., this paper presents a case study of the cost effectiveness of gully remediation at six properties across the Fitzroy. Our results reveal a broad range of cost effectiveness among these sites, highlighting the importance of both the selection of policy mechanism and the need for targeted remediation measures. The pattern of cost effectiveness for these sites also raises the possibility of economies of scale in gully work, which could indicate funding advantages from targeting projects that address large volumes of gully erosion. Finally, the magnitude of the costs per unit of sediment reduction at these sites indicates the need to consider a broad spectrum of policy responses to reduce sediment export to the reef.